1998
DOI: 10.1136/jmg.35.2.146
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of an inverted X chromosome (p11.2q21.3) associated with mental retardation using FISH.

Abstract: We report on a patient with a pericentric inversion of the X chromosome, 46,Y,inv(X)(p11.2q21.3), who was referred for cytogenetic analysis because of mild mental retardation, short stature, prepubescent macro-orchidism, and submucous cleft palate. The same chromosomal abnormality was found in the proband's mother. The inverted X chromosome was late replicating in all the mother's lymphocytes studied, indicative of a likely unbalanced inversion. We show, by fluorescence in situ hybridisation (FISH) using a pan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
1
1

Year Published

1999
1999
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 26 publications
0
6
1
1
Order By: Relevance
“…All reported patients were women with short stature, secondary amenorrhoea or oligomenorrhea, and premature ovarian failure [Maraschio et al, 1996], except one male fetus (spontaneous abortion) without fetal pathological data [Allderdice and Eales, 1981]. A single report of a man with a pericentric inversion Xp11.2-Xq21.3, partial GHD, and MR fits with an interrupted gene in the breakpoint region of Xq21.3 [Sloan-Bena et al, 1998]. In this region, men with small cytogenetically visible duplications have also been described [Shapira et al, 1997].…”
Section: Discussionmentioning
confidence: 91%
“…All reported patients were women with short stature, secondary amenorrhoea or oligomenorrhea, and premature ovarian failure [Maraschio et al, 1996], except one male fetus (spontaneous abortion) without fetal pathological data [Allderdice and Eales, 1981]. A single report of a man with a pericentric inversion Xp11.2-Xq21.3, partial GHD, and MR fits with an interrupted gene in the breakpoint region of Xq21.3 [Sloan-Bena et al, 1998]. In this region, men with small cytogenetically visible duplications have also been described [Shapira et al, 1997].…”
Section: Discussionmentioning
confidence: 91%
“…Fragile X molecular studies were negative. DNA replication studies on maternal peripheral blood showed skewed X inactivation of the inverted X, suggesting an unbalanced inversion [Sloan-Bena et al, 1998]. In a study of a three-generation family, the inv(X)(p21.1q26) cosegregated with Duchenne muscular dystrophy, suggesting disruption of the gene at the Xp21.1 breakpoint.…”
Section: Discussionmentioning
confidence: 99%
“…Heterozygotes with a X chromosome pericentric inversion may have four possible X gametic types [X, inv(X), dup(p)/del(q) and dup(q)/del(p)], and may cause abnormal offspring or recurrent abortions. Males with gene deletions or duplications in the Xq13→q21.3 region or even extending to Xq24 region may have mental retardation, short stature, growth retardation, hypogonadism and general muscle hypotonia 23 24…”
Section: Introductionmentioning
confidence: 99%